Tingkat Keterampilan Renang Gaya Dada Jarak 25 Meter Pada Siswa Kelas IV Sekolah Dasar - Lisa Sulistiyana; Supriyono; Cahyo Yuwono; Bhayu Billiandri (Indonesian Journal for Physical Education and Sport, 2024)
The background of the problem in this study is that there are still fourth grade students at SD N Supriyadi 1 who are afraid when doing breaststroke swimming. As a result, the child's ability is very difficult to develop. In general, students' swimming skills still need to be improved, especially from the technical aspect. The purpose of this study was to determine the level of breaststroke swimming skills at a distance of 25 meters for fourth grade students of SD Supriyadi 1 Semarang City in 2024. This research is a quantitative descriptive study using a one-shot case study design with data collection techniques through survey tests using research instruments. The subjects of this study were fourth grade students of SD Supriyadi 1 Semarang City. The results of the study obtained an overall percentage in the good category there are 4 students (16%) while the sufficient category there are 21 students (84%) and the less category there are no students or (0%). Students who fall into the sufficient category are mostly due to children who are less serious in doing breaststroke swimming, so that the swimming techniques performed are wrong. In addition, another factor that influences is the fear of students when doing breaststroke swimming as far as 25 meters. The conclusion from the results of the study is that the level of 25-meter breaststroke swimming skills of fourth grade students of SD Supriyadi 1 Semarang City in 2024 is in the moderate category.